2021
DOI: 10.1155/2021/9720297
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Process of Injection Molding and Optimization for Automobile Instrument Parameter in Embedded System

Abstract: The automobile instrument is the indispensable item that is essential to keep the driver conversant of the process of the engineer and the other system. There are different parameters involved in the automobile instrument, which requires a different process involved in creating the automobile parameter. This research is designed to show the simulation development of injection molding and optimization of automobile instrument parameters using different optimization techniques. In this paper, Taguchi Orthogonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…ey used MATLAB to build a function to solve the optimization problem and finally obtain the optimal combination of process parameters. Ramesh et al [9] used matrix design and parameter group algorithms to investigate the variety combination of parameters for the automotive instrumentation injection molding process and verified this using processing experiments.…”
Section: Introductionmentioning
confidence: 99%
“…ey used MATLAB to build a function to solve the optimization problem and finally obtain the optimal combination of process parameters. Ramesh et al [9] used matrix design and parameter group algorithms to investigate the variety combination of parameters for the automotive instrumentation injection molding process and verified this using processing experiments.…”
Section: Introductionmentioning
confidence: 99%
“…(Mukras, 2020) employed the kriging technique, an optimization approach to minimize the product cycle time generated by volumetric shrinkage and warpage of injection molded products using an experimentalbased optimization approach. (Ramesh et al, 2021) employed Taguchi orthogonal parameter design and particle swarm optimization to measure the shrinkage volume and warpage amount rate for automobile molded parts. (Azdast & Hasanzadeh, 2019) comprehensively investigated the shrinkage behavior of polycarbonate parts using response surface methodology in different conditions based on the design of experiments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ramesh et al, [3] demonstrated the simulation of injection moulding development and the optimization of vehicle instrument characteristics using various optimization approaches. The shrinkage volume rate and warpage quantity rate are measured using Taguchi Orthogonal parameter design and particle swarm optimization (PSO) in this paper.…”
Section: Introductionmentioning
confidence: 99%